LEVELS OF ANGIOGENESIS-REGULATORY CHEMOKINES IN THE SYNOVIAL FLUID OF PATIENTS WITH RHEUMATOID ARTHRITIS - D. A. Zhebrun; A. L. Maslyansky; A. G. Titov; A. P. Patrukhin; A. A. Kostareva; I. S. Goltseva; N. A. Arsentyeva; N. E. Lyubimova; A. A. Totolyan (Научно-практическая ревматология)
The role of chemokines in the immunopathogenesis of rheumatoid arthritis (RA) has been actively investigated in recent years. Angiogenic and angiostatic chemokines are important mediators of angiogenesis in the development and extent of pannus. Peripheral blood and synovial fluid (SF) is a major biomaterial in clinical and immunological studies. At the same time, it is the SF test that may yield the most informative results since that gives an idea of the processes that occur locally within a joint. Objective: to perform a comparative analysis of the levels of a number of CXC, CC, and CX3C chemokines in the SF of patients with RA, osteoarthritis (OA), and joint injuries. Subjects and methods. The multiplex analysis using xMAP technology (Luminex, USA) was used to analyze levels of CXC, CC, and CX3C chemokines in SF and serum of patients with RA (n = 20), OA (n = 9) and controls (n = 9). Results and discussion. The SF levels of CCL24/eotaxin-2, as well as those of the angiostatic chemokines CXCL9/MIG, CXCL10/IP10, CXCL11/ITAC, and CXCL13/BCA-1 were higher in the RA group than in the control and OA groups. There was a direct correlation between SF levels of CCL5/RANTES and DAS28, as well as patient global disease activity assessment on visual analogue scale, and that between the level of CCL2/MCP-1 in the SF and that of anticyclic citrullinated peptide (anti-CCP) antibodies in the serum. The SF concentrations of CXCL5/ENA78 and CXCL7/NAP-2 were shown to depend on the presence of serum anti-CCP. Serum CXCL13/BCA-1 levels were higher in RA than those in OA, as that of CXCL7/NAP-2 than in the control group.